The Schur-Convexity of the Generalized Muirhead-Heronian Means - Yong-Ping Deng; Shan-He Wu; Yu-Ming Chu; Deng He (Abstract and Applied Analysis, 2014)
We give a unified generalization of the generalized Muirhead means and the generalized Heronian means involving three parameters. The Schur-convexity of the generalized Muirhead-Heronian means is investigated. Our main result implies the sufficient conditions of the Schur-convexity of the generalized Heronian means and the generalized Muirhead means.